Crystal structure of the N-myristoylated lipopeptide-bound MHC class I complex - Daisuke Morita (Nature Portfolio, 2016)
Lipid antigens have been added to the antigenic repertoire in recent years. Here, the authors have identified Mamu-B*098 as a lipopeptide antigen presenting molecule and using structural and biochemical analysis have shown that it has a different antigen binding pocket to previously analysed proteins.